Impact of Combined Operation of CVR and Energy Storage System in Distribution Grid - Singh S.; Babu P.V.; Singh S.P. (My University, 2025)
An investigation on the impact of the combined operation of Conservation of Voltage Reduction (CVR) and Energy Storage System (ESS) in distribution grid has been reported in this paper. A smart grid-enabled Volt/VAr Control (SG-VVC) based approach has been utilized to perform the CVR operation in presence of ESS. The main part of SG-VVC is the Volt/VAr optimization (VVO) engine that can perform numerous tasks for the advance distribution management system (ADMS) with the coordination of control centre operator. In this study, the main task of the VVO is to capitalize the CVR benefits (in terms of energy savings and voltage reduction range) by minimizing the total substation power demand through optimal settings of VVC parameters. To achieve the optimal VVC solution, a gravitational search algorithm driven VVO method has been utilized. The test system has been simulated for two cases as with and without ESS system. In each case, operation of test system is carried out with and without VVO mode considering different loadings such as light, normal and high loading conditions. The outcomes of simulated results demonstrated that significant improvement in peak load demand reduction has been achieved by proposed VVO including the ESS with reduced system losses and acceptable feeder voltage profile. © 2018 IEEE.